The morphological complexity of L1 Arabic-speaking children - Issa, Iyad (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2019)
Spelling poses a challenge to Arabic-speaking learners due to the complexity of the morphological and orthographic system in Arabic. Arabic morphology has been argued to play a critical role in spelling since its morphological operations are built on a system consisting of a root that is interlocking into different patterns of vowels to form different categories of words. In addition, Arabic orthography is considered to be loyal to the morphographic principle (Ravid, 2012), where morphemes correspond to graphic representation regardless of the pronunciation, especially in the non-vowelized texts. This study made a detailed classification of spelling errors in a word dictation task, based on morphological structures, undertaken by 107 Typically-developing learners (TD) and learners with learning disabiities (LD) attending the same schools. All participants ranged in age from 7 years, 3 months to 15 years, 2 months (grades 2 to 8). The spelling task was made up of 400 common words representing all morphological forms in different conjugations and grammatical classes. The results indicated that learners made three types of errors: errors with respect to the root, errors with respect to the word pattern, and errors with respect to both the root and the word pattern. The results also showed that TD and LD learners follow a similar pattern of complexity even though the LD group produced more errors than the TD group. The results revealed that MA and PA exhibited significant positive regression (b= 9.398, 16.106 respectively) with spelling, indicating that learners with higher scores in PA and MA have higher scores in spelling. The results argued for the crucial contribution that morphological awareness makes towards the general spelling abilities among learners and provide additional evidence for the nonlinear growth of morphological knowedge in spelling. In addition, spelling errors suggested that the spelling process goes in a hierarchical way where words can be accessed and processed either according to the root or according to the stem. Intact verbs are processed according to their root and word pattern. Some weak verb forms, whose radicals undergo modifications, are processed according to their stem, while those whose radicals are fully represented in the spoken word, are processed according to their root and word patterns. Therefore, roots or stems are firstly accessed and attached to basic word patterns (the grapheme without diacritics and affixes). Thereafter, prefixes and, then, suffixes are attached to the word pattern and, finally, diacritics are accessed and attached to the word pattern.
Keywords: Cognition in children; Reading; Arabic language -- Orthography and spelling; Arabic language -- Orthography and spelling -- Study and teaching; Arabic language -- Study and teaching; Arabic language -- Phonetics